STATUS OF TRIBAL RIGHTS DURING THE COLONIAL PERIOD - Rohit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Since the 1990s, issues related to forests (recognising the traditional rights of tribal communities on forests, bringing forest wealth under the purview of village panchayats and giving autonomy to forest-dependent communities for the use of forest resources) have gained momentum. On one hand, the atmosphere of rebellion keeps heating up in various parts of the country regarding ’community rights’ on forests. On the other hand, the tribals were looted by the UPA government under the guise of law. For example, laws were made by the governments to control forests, but at the cost of economic exclusion of the tribals. Thus, whenever it comes to issues related to tribals, we should always keep in mind that the problems of tribals have not arisen today or yesterday, but it has been going on since the colonial period. When, in the guise of modernisation and commercialisation, forests became a field of exploitation and earning by the British to extract more revenue and natural resources to migrate to Europe. Especially with regard to the wood used for timber and railway sleepers, the forest dwelling communities were deprived of their traditional forest rights